2014
DOI: 10.4238/2014.march.12.15
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the nucleolus organizing regions in Loricaria cataphracta (Siluriformes, Loricariidae) of the upper Paraguay River basin indicate an association with transposable elements

Abstract: ABSTRACT.A cytogenetic analysis of Loricaria cataphracta revealed a diploid number of 2n = 64 chromosomes, distributed as 12 metacentric + 8 submetacentric + 2 subtelocentric + 42 acrocentric, with a fundamental number of 86. Analysis of the nucleolus organizing region (NOR) using silver nitrate impregnation and fluorescence in situ hybridization (18S rDNA probe) techniques showed intra-population chromosomal polymorphism that could be classified into five different patterns

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…For the latter two species, the authors proposed that fusion events are the most plausible explanation for the observed structural and numerical polymorphisms, since the increase in the number of biarmed chromosomes is correlated with the decrease in 2n. In R. lanceolata and R. latirostris, this hypothesis was confirmed by the presence of interstitial telomeric sequences (ITSs) or other repetitive sequences in the predicted fusion points(Giuliano-Caetano, 1998;Porto, Gindri et al, 2014;Glugoski et al, 2022).The presence of monoarmed chromosomes is a common feature in Rineloricaria and the karyotype of R. teffeana studied herein also fits this pattern. However, the exclusive presence of acrocentric chromosomes combined with low 2n is exceptional and has not yet been reported for the genus.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…For the latter two species, the authors proposed that fusion events are the most plausible explanation for the observed structural and numerical polymorphisms, since the increase in the number of biarmed chromosomes is correlated with the decrease in 2n. In R. lanceolata and R. latirostris, this hypothesis was confirmed by the presence of interstitial telomeric sequences (ITSs) or other repetitive sequences in the predicted fusion points(Giuliano-Caetano, 1998;Porto, Gindri et al, 2014;Glugoski et al, 2022).The presence of monoarmed chromosomes is a common feature in Rineloricaria and the karyotype of R. teffeana studied herein also fits this pattern. However, the exclusive presence of acrocentric chromosomes combined with low 2n is exceptional and has not yet been reported for the genus.…”
supporting
confidence: 77%
“…For the latter two species, the authors proposed that fusion events are the most plausible explanation for the observed structural and numerical polymorphisms, since the increase in the number of biarmed chromosomes is correlated with the decrease in 2 n . In R. lanceolata and R. latirostris , this hypothesis was confirmed by the presence of interstitial telomeric sequences (ITSs) or other repetitive sequences in the predicted fusion points (Giuliano‐Caetano, 1998; Porto, Gindri et al ., 2014; Glugoski et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering this restricted distribution to the Amazonian system, we also assume that there was a mistake in the identification of populations previously diagnosed as L. cataphracta, coming from the Coxim River (Upper Paraguay river). 33 When compared with L. simillima, such specimens share some characteristics (e.g., 2n = 64, heterochromatin pattern); however, they exhibit a marked numerical and structural polymorphism of NOR sites. This is a condition until then, exclusive to this population, which can be interpreted as (1) a population variation; (2) an error in taxonomic identification, these specimens may be other species that occur in the Coxim River basin (e.g., Loricaria apeltogaster or Loricaria coximensis); or (3) an undescribed species that is morphologically related to the L. cataphracta complex.…”
Section: Cytotaxonomic Features Of the Major Clades Belonging To Lorimentioning
confidence: 99%
“…28 Moreover, this group has supernumerary chromosomes, 24,35,40 differentiated sex chromosomes, 23,25,30 and intrapopulational polymorphisms in diploid number and karyotypic formulas [42][43][44] and in distribution of ribosomal DNA (rDNA) sites. 33 This study consists of the first review and comparative analysis involving species of Loricariinae from different Brazilian watersheds. Our study aimed to hypothesize the chromosome evolution as well as to fill in the gap of cytotaxonomic knowledge to clarify the relationships of conflicted groups in Loricariini tribe.…”
Section: Introductionmentioning
confidence: 99%